Analytical Study of the Contribution of Muslim Scientists to the Development of Science in Islamic Civilization: A Literature Study - Azis, Abdul; Husaini, Husaini; Azmi, Nurul; Renida, Maisuri; Safitri, Eka Deviana (Lembaga Teewan Journal Solutions, 2026)
This research aims to comprehensively elaborate on the significant contributions of Muslim scientists to the development of science during the Islamic golden age and analyze its relevance to contemporary modern civilization. The background of this study is rooted in the existence of a fairly deep historical bias in the historical narrative of global science, which often ignores the phase of intellectual transmission of the Islamic world and jumps directly from the period of ancient Greece to the Renaissance era in Western Europe. The research method used in this article is qualitative descriptive based on library research by analyzing in depth fifteen reputable and relevant scientific journals. The results show that (1) Muslim scientists not only acted as translators of ancient classical texts, but also as major innovators, (2) true experimentalists, and (3) laid the foundations of modern scientific methodology in various crucial fields such as mathematics, medical science, astronomy, chemistry, pharmacy, and philosophy. The findings of this scientific article indicate that the integration of classical Islamic scientific traditions into modern educational curricula is able to substantively revitalize students' motivation to learn science and strengthen the morality-based character of spirituality in the digital age.